Synthesis and Characterization of Photoresponsive Macromolecule for Biomedical Application - Pang, Juan; Gao, Ziyu; Zhang, Long; Wang, Huiming; Hu, Xiaohong (Frontiers in Chemistry, 2018)
Azobenzenes, a photo switcher, has attracted increasing interest due to their structural response upon photo stimulus in the field of information science and chemical sensing for recent decades. However, limited water solubility and cytotoxicity restrained their applications in biomedical field. In the research, HA-AZO was designed to a water-soluble photo switcher in biomedical application. Synthesized HA-AZO had good water-solubility and a stable π-π* transition absorbance peak trans-isomer. Upon UV, transformation from trans-isomer to cis-isomer of HA-AZO could be realized according to UV spectra. Reversely, trans-isomer could be gradually recovered from cis-isomer in dark. Simultaneously, quick response and slow recovery could be detected in the process of structural change. Moreover, repeated illumination was further used to detect antifatigue property of HA-AZO, which showed no signal of fatigue during 20 circles. The influence of pH value on UV spectrum for HA-AZO was investigated in the work. Importantly, in acid solution, HA-AZO was no longer showed any photo-responsive property. Additionally, the status of HA-AZO under the effect of UV light was investigated by DLS results and TEM image. Finally, in vitro cytotoxicity evaluations were performed to show the effects of photoresponsive macromolecule on cells.